2020
DOI: 10.17221/31/2019-vetmed
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of infection with N protein-specific Immunoglobulin M and G in naturally occurring distemper in dogs

Abstract: In dogs, canine distemper has a worldwide distribution with high morbidity/mortality, despite the widespread usage of vaccines and has no specific treatment. In susceptible animals with the canine distemper virus, respiratory, gastrointestinal and nervous system disorders, immunosuppression and cutaneous lesions can also be seen. Especially puppies and unvaccinated dogs are prone to get the viral infection. IgM and IgG antibodies constitute the major component of the natural antibodies produced during the prim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 20 publications
(30 reference statements)
0
7
0
Order By: Relevance
“…CDD is over all world distribution with highly morbidity/mortality in spite of vaccinated animals and has no specific treatment (7). In this study different forms of CDV inclusion bodies were detected within erythrocytes and neutrophils based on microscopic examination of blood smears.…”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations
“…CDD is over all world distribution with highly morbidity/mortality in spite of vaccinated animals and has no specific treatment (7). In this study different forms of CDV inclusion bodies were detected within erythrocytes and neutrophils based on microscopic examination of blood smears.…”
Section: Discussionmentioning
confidence: 81%
“…In addition, Acosta-Jamett et al (27) revealed that a maintained canine population management and pet possession are the only arrangements to reduce canine population, which would, in turn, reduce canine-wildlife interactions and outcomes pathogen spreading. On the other hand, Saltik and Kale, (7) and Dorji et al (15) mentioned that no significant difference in the prevalence of CDD between stray and pet dogs. In particular, vaccination programmes for pet dogs are more used in private veterinary clinics.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…RNA of infectious agents is successfully extracted from various biological fluids, tissues, and from the environment such as soil, water, and food. PCR is effective in detecting bacteria, fungi, parasites, and viruses ( Saltik & Kale, 2020;Worsley-Tonks et al, 2021). R. Uakhit et al (2022) state that the PCR method is characterised by a sensitivity sufficient to detect 10-100 pg of viral RNA in a sample.…”
Section: Discussionmentioning
confidence: 99%